2004
DOI: 10.1074/jbc.m310160200
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Mitochondrial Proteome, a Study of Fermentative and Respiratory Growth

Abstract: Saccharomyces cerevisiae is able to switch from fermentation to respiration (diauxic shift) with major changes in metabolic activity. This phenomenon has been previously studied on the transcriptional level. Here we present a parallel analysis of the yeast mitochondrial proteome and the corresponding transcriptional activity in cells grown on glucose (fermentation) and glycerol (respiration). A two-dimensional reference gel for this organelle proteome was established (available at www.biochem.oulu.fi/proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
141
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 85 publications
(66 reference statements)
15
141
1
4
Order By: Relevance
“…In the case of various CYP and glutathione S-transferase proteins, detailed analysis of targeting mechanism shows a need for the activation of chimeric MT-targeting signals by physiological factors (9 -11, 14). These results on bimodal targeting are also supported by recent proteomic data showing a large number of proteins identified as part of mitochondrial proteome are also localized to extramitochondrial compartments, including the cytosol, peroxisomes, and ER membrane (5)(6)(7)(8). It is therefore highly likely that the bimodal targeting, driven by chimeric NH 2 -terminal signals as shown for various CYP and glutathione S-transferase enzymes, represents a precisely evolved physiological process with functional significance.…”
Section: Erod Erndsupporting
confidence: 67%
See 1 more Smart Citation
“…In the case of various CYP and glutathione S-transferase proteins, detailed analysis of targeting mechanism shows a need for the activation of chimeric MT-targeting signals by physiological factors (9 -11, 14). These results on bimodal targeting are also supported by recent proteomic data showing a large number of proteins identified as part of mitochondrial proteome are also localized to extramitochondrial compartments, including the cytosol, peroxisomes, and ER membrane (5)(6)(7)(8). It is therefore highly likely that the bimodal targeting, driven by chimeric NH 2 -terminal signals as shown for various CYP and glutathione S-transferase enzymes, represents a precisely evolved physiological process with functional significance.…”
Section: Erod Erndsupporting
confidence: 67%
“…It remains to be determined if this step is also an important regulatory step that determines the extent of MT targeting. It is becoming increasingly apparent that mitochondria from lower eukaryotes as well as from mammalian cells contain a large number of proteins that were previously thought to be exclusively extramitochondrial in their location and function (5)(6)(7)(8). It is estimated that nearly 50% of the Ͼ1500 proteins associated with mammalian mitochondria may lack canonical mitochondrial-targeting signals.…”
Section: Erod Erndmentioning
confidence: 99%
“…The known assembly factors involved in copper ion metallation of CcO are not likely to contribute to the mitochondrial copper pool because they are low abundance proteins. A recent mitochondrion proteomic study showed Sco1 to be a low abundant protein comparable in levels of the CcO subunit Cox6 (42).…”
Section: Resultsmentioning
confidence: 99%
“…The purity of organelles and other protein complexes is crucial to subcellular proteome research [13][14][15][16][17]. For the isolation of subcellular structures and organelles several methods, such as differential-and density-gradient centrifugation [18][19][20], immunoisolation [8], affinity purification, [21], and freeflow electrophoresis [22], have been applied. It has been shown that such fractionations improved identification of proteins from targeted subcellular structures [8,10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%